Systematics, revisionary taxonomy, and biodiversity of Afrotropical Lithocolletinae (Lepidoptera: Gracillariidae) - de Prins, Jurate; Kawahara, Akito Y. (Zootaxa, 2012)
Afrotropical Lithocolletinae are known from 26 described species, mainly from southern Africa. In the present study we describe 41 new species, bring to 66 the number of species from this geographical region. The new species include: Hyloconis luki De Prins, n. sp., Neolithocolletis mayumbe De Prins, n. sp., N. nsengai De Prins, n. sp., Cameraria fara De Prins, n. sp., C. landryi De Prins, n. sp., C. perodeaui De Prins, n. sp., C. sokoke De Prins, n. sp., C. torridella De Prins, n. sp., C. varii De Prins, n. sp., C. zaira De Prins, n. sp., Phyllonorycter aarviki De Prins, n. sp., P. achilleus De Prins, n. sp., P. acutulus De Prins, n. sp., P. adderis De Prins, n. sp., P. agassizi De Prins, n. sp., P. albertinus De Prins, n. sp., P. dombeyae De Prins n. sp., P. fletcheri De Prins, n. sp., P. gato De Prins, n. sp., P. grewiaephilos De Prins, n. sp., P. hibiscola De Prins, n. sp., P. ipomoellus De Prins, n. sp., P. jabalshamsi De Prins, n. sp., P. kazuri De Prins, n. sp., P. maererei De Prins, n. sp., P. mida De Prins, n. sp., P. mwatawalai De Prins, n. sp., P. ocimellus De Prins, n. sp., P. ololua De Prins, n. sp., P. rongai De Prins, n. sp., P. ruizivorus De Prins, n. sp., P. ruwenzori De Prins, n. sp., P. silvicola De Prins, n. sp., P. trochetellus De Prins, n. sp., P. tsavensis De Prins, n. sp., P. turensis De Prins, n. sp., P. umukarus De Prins, n. sp., Cremastobombycia morogorene De Prins, n. sp., C. kipepeo De Prins, n. sp., Porphyrosela desmodivora De Prins, n. sp., P. gautengi De Prins, n. sp. Furthermore, Cameraria hexalobina (Vári, 1961), n. comb. is transferred from Phyllonorycter to Cameraria, and a neotype for Porphyrosela homotropha Vári, 1963 is designated. Lithocolletis aurifascia Walker, 1875, previously placed in Phyllonorycter, is excluded from Lithocolletinae. We designate lectotypes where necessary and provide morphological descriptions of males and females, information on host plants, and detailed distribution data. We also include dichotomous keys to species groups and species, accompanied by DNA barcode sequences of 19 species. We also discuss generic relationships within Lithocolletinae based on both morphology and molecules with a special emphasis on Afrotropical taxa.